Longitudinal online diaries with dental practitioners and dental care professionals during the COVID-19 pandemic: A trajectory analysis - Laura Beaton; Jennifer Knights; Lorna Barnsley; Mariana Araujo; Jan Clarkson; Jan Clarkson; Ruth Freeman; Linda Young; Siyang Yuan; Gerry Humphris (Frontiers Media S.A., 2022)
IntroductionThe COVID-19 pandemic resulted in a series of significant changes and adjustments within dentistry, as dental professionals dealt with temporary closures of dental practices, increased use of personal protective equipment, a reduction of clinical procedures, and extensions to training programmes. Recent research has illustrated the impact of the pandemic on the dental profession, indicating that many dental professionals felt emotionally exhausted and experienced significant uncertainty and anxiety. This qualitative study aimed to understand how these experiences and emotions changed over the course of six months, in dental trainees and primary dental care staff in Scotland.MethodsA longitudinal diary study was conducted (June-December 2020) with dental trainees and primary dental care staff. The diary asked respondents to answer three questions related to their emotional exhaustion, on a weekly basis. There was also an open question asking respondents to describe any significant issues or concerns they had experienced during the preceding week because of the impact of the COVID-19 pandemic on their work or training. This qualitative data was explored using a trajectory analysis approach to determine specifically changes over time.ResultsThe trajectory analysis revealed several key concerns prevalent amongst respondents, and how they fluctuated over the six months. Concerns included: the impact of the pandemic on respondents' future careers and on dentistry more generally; adapting to new working environments; the impact on their patients' dental treatment and oral health; the impact on their health and wellbeing; financial considerations and adjusting to new safety measures as part of the remobilization of dental services.DiscussionIn the second half of 2020, as the UK was adjusting to the introduction of new COVID-19 safety measures in everyday life, the dental profession were grappling with significant changes to their working environment, including PPE, redeployment, use of aerosol generating procedures (AGPs), and timelines for re-opening practices. This longitudinal diary study has shown some parts of the dental profession in Scotland expressed very varied and personal concerns and anxieties related to COVID-19. Respondents' candor in their diary entries revealed explicit, frequent and high levels of uncertainty and worry related to their training and career. Collectively, the data corpus highlighted the emotional toll these anxieties have taken on the dental professions in Scotland.ConclusionThese findings demonstrate the need for (a) increased provision of mental health and wellbeing support services for dental staff and (b) the study of the linkage between organization of pandemic management to the working practices of staff delivering services. Interventions, at various levels, should take into consideration the fluctuating nature of dental professionals' concerns and anxieties over time, to address both immediate and longer-term issues.